2005
DOI: 10.1055/s-2005-869524
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of CS-747 (prasugrel, LY640315), a Novel, Potent Antiplatelet Agent with in Vivo P2Y12Receptor Antagonist Activity

Abstract: CS-747 (prasugrel, LY640315) is a member of the thienopyridine class of oral platelet aggregation inhibitors that includes ticlopidine and clopidogrel. A single oral administration of CS-747 produced a dose-related inhibition of platelet aggregation in rats that was approximately 10- and 100-fold more potent than that of clopidogrel and ticlopidine, respectively. The antiaggregatory effect of CS-747 was evident at 30 minutes and lasted until 72 hours after dosing, indicating fast onset and long duration of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
158
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(172 citation statements)
references
References 35 publications
7
158
0
3
Order By: Relevance
“…Preclinical studies indicate that like clopidogrel, prasugrel is a prodrug that requires metabolic conversion to an active metabolite [19]. Following oral dosing of prasugrel, there is a rapid and potent inhibition of ADP-induced platelet activation and aggregation [19,22,23]. These early studies demonstrated that the dose required to achieve a given degree of platelet inhibition or inhibition of thrombus formation in preclinical models was approximately one-tenth and one-hundredth that of clopidogrel and ticlopidine, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Preclinical studies indicate that like clopidogrel, prasugrel is a prodrug that requires metabolic conversion to an active metabolite [19]. Following oral dosing of prasugrel, there is a rapid and potent inhibition of ADP-induced platelet activation and aggregation [19,22,23]. These early studies demonstrated that the dose required to achieve a given degree of platelet inhibition or inhibition of thrombus formation in preclinical models was approximately one-tenth and one-hundredth that of clopidogrel and ticlopidine, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, a novel thienopyridine P2Y 12 inhibitor, prasugrel (CS-747, LY640315), has been identified and profiled [19][20][21][22][23]. Preclinical studies indicate that like clopidogrel, prasugrel is a prodrug that requires metabolic conversion to an active metabolite [19].…”
Section: Introductionmentioning
confidence: 99%
“…Prasugrel is a thienopyridine adenosine diphosphate (ADP) receptor antagonist prodrug that rapidly converts to an inactive metabolite (R-95913) by carboxyesterase and cannot be detected in plasma. The conversion of R-95913 to R-138727 is catalyzed by cytochrome P450 enzymes ( Figure 1); R-138727 binds specifically and irreversibly to the P2Y 12 ADP receptor and inhibits platelet activation and aggregation for the remainder of the life of the platelet [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are therefore required to better understand the role for P2Y 12 inhibition in controlling ischemic limb complications in patients with PAD. Prasugrel, a third‐generation thienopyridine antiplatelet agent used clinically to treat patients with acute coronary syndrome who are undergoing percutaneous coronary intervention,13 has been shown to provide effective inhibition of platelet activation and aggregation via the selective inhibition of platelet P2Y 12 14, 15. Furthermore, it has also been shown to be more potent and consistent than clopidogrel for P2Y 12 inhibition 16.…”
Section: Introductionmentioning
confidence: 99%